(untitled) (Journal of Informatics Education and Research, 2024)
This study seeks to quantify how altering pricing methods affect consumer behavior in E - pharmacy and OTT industries. In Bangalore City a questionnaire was handed out and 600 responses or 79.8% of the total were returned. No statistically significant differences relating to demographic or socioeconomic characteristics were found, although the results did demonstrate a beneficial association between pricing methods and customer behavior.